1998
DOI: 10.1177/156482659801900104
|View full text |Cite
|
Sign up to set email alerts
|

Food Aversions and Cravings during Pregnancy: Prevalence and Significance for Maternal Nutrition in Ethiopia

Abstract: A cross-sectional study of the nutritional significance of food aversions and cravings during pregnancy was conducted on 295 women in southern Ethiopia between February and May 1995. A questionnaire was used to collect data on dietary practices. Mid-upper-arm circumference (MUAC), triceps skinfold thickness (TSFT), and weight measurements were used to assess nutritional status. Slightly fewer than three-quarters (71%) of the women craved one or more foods, whereas about two-thirds (65%) avoided at least one fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 6 publications
(13 reference statements)
8
35
3
Order By: Relevance
“…They contend that some cravings signal nutritional deficiencies so that the response becomes a mechanism to meet the bodies' need for extra calories. More so, cravings may be due to changing sensitivities, smell and tastes during pregnancy [26]. These findings agree with Crystal et al [4] who reported that women with severe nausea showed no association with cravings.…”
Section: Cravings and Morning Sicknesssupporting
confidence: 82%
“…They contend that some cravings signal nutritional deficiencies so that the response becomes a mechanism to meet the bodies' need for extra calories. More so, cravings may be due to changing sensitivities, smell and tastes during pregnancy [26]. These findings agree with Crystal et al [4] who reported that women with severe nausea showed no association with cravings.…”
Section: Cravings and Morning Sicknesssupporting
confidence: 82%
“…Demissie et al (1998) proposed that, among pregnant women with limited access to food, aversions to staple foods would increase dietary diversity and access to micronutrients, a hypothesis supported by some studies (A. G. Young & Pike, 2012) but not others (Placek & Hagen, 2015).…”
Section: Study Goals and Predictionsmentioning
confidence: 99%
“…Some studies in populations facing resource scarcity, however, have failed to support it. A study in southern Ethiopia for example, found that pregnant women avoided cereals, which were non-toxic staple foods, but craved meat and other livestock products, which were scarce (Demissie, Muroki, & Kogi-Makau, 1998). In Turkana pastoralists, I.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food taboos refer to those foods which are strictly forbidden for health, cultural, and religious reasons [13,14,15,16]. In Ethiopia, food taboos are thought to have been established during pregnancy as a means of protecting the health of women and their babies.…”
Section: Introductionmentioning
confidence: 99%